2009
DOI: 10.1016/j.ygeno.2008.11.004
|View full text |Cite
|
Sign up to set email alerts
|

An autosomal genetic linkage map of the domestic cat, Felis silvestris catus

Abstract: We report on the completion of an autosomal genetic linkage (GL) map of the domestic cat (Felis silvestris catus). Unlike two previous linkage maps of the cat constructed with a hybrid pedigree between the domestic cat and the Asian leopard cat, this map was generated entirely with domestic cats, using a large multi-generational pedigree (n=256) maintained by the Nestlé Purina PetCare Company. Four hundred eighty-three simple tandem repeat (STR) loci have been assigned to linkage groups on the cat’s 18 autosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
1

Year Published

2009
2009
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 39 publications
3
28
0
1
Order By: Relevance
“…Divergence in regions harboring homologous recombination genes (RAD51B, ZFYVE26, BRCA2) may contribute to the high recombination rate reported for domestic cats relative to other mammals (59). Previous studies have suggested that domestication may select for an increase in recombination as a mechanism to generate diversity (60).…”
Section: Resultsmentioning
confidence: 99%
“…Divergence in regions harboring homologous recombination genes (RAD51B, ZFYVE26, BRCA2) may contribute to the high recombination rate reported for domestic cats relative to other mammals (59). Previous studies have suggested that domestication may select for an increase in recombination as a mechanism to generate diversity (60).…”
Section: Resultsmentioning
confidence: 99%
“…Fca-6.2 is anchored to chromosome coordinates with two physical framework maps, a radiation hybrid map [3] and a short tandem repeat (STR) linkage map [4]. Further, 1943 distinct sites identified in a recently built linkage map using a single nucleotide polymorphism (SNP) genotyping array including ≈60,000 SNPs from an Illumina custom cat genotyping array are also mapped to the assembly.…”
Section: Data Descriptionmentioning
confidence: 99%
“…Additionally, some of the older maps may underestimate the size if they do not cover the entirety of the X chromosome. Similarly, the recombination length of the domestic cat autosomal map is longer than that observed in most reported mammalian maps (Menotti-Raymond et al 2008).…”
Section: Resultsmentioning
confidence: 68%